Investigation of the Self‐Doping Process in HgSe Nanocrystals. Issue 3 (13th September 2017) - Livache, Clément; Martinez, Bertille; Robin, Adrien; Goubet, Nicolas; Dubertret, Benoit; Wang, Hongyue; Ithurria, Sandrine; Aubin, Hervé; Lhuillier, Emmanuel
Abstract : Colloidal nanocrystals are an interesting platform for the design of low cost infrared optoelectronic materials. In addition to the conventionally observed interband features, doped nanocrystals present intraband transitions, which expand the possibilities for electronic spectrum engineering. In this paper, the recent results obtained in the field of mercury chalcogenides self‐doped nanocrystals presenting absorption features in the mid infrared range are reviewed. In particular, the results relative to the synthesis, control of doping and transport properties of HgSe colloidal nanocrystals are discussed. Abstract : This short review discusses recent results on self‐doped HgSe nanocrystals from the material synthesis up to the device intergration, and includes the physical discussion of the doping process.